What Obstacles Stands in the Way of the Achievement of Socialism - Jossa, Bruno (Archives of Business Research, 2023)
The aim of this paper is to show that a system of democratically managed firms is the model of socialism best tailored to human nature. From the author’s perspective, considering that the retention of markets in such a system allows selfish drives of individuals to act themselves out to the full, its establishment would come up against fewer obstacles than those standing in the way of the creation of a centrally planned one. An additional thesis advanced in the paper is that that the process leading to the advent of such a system can be looked upon as a socialist revolution consistent with the principles of Darwinian evolutionism.